SUSTAINABLE TOURISM PADA TAMAN SOEKASADA UJUNG KARANGASEM - Mahastuti, Ni Made Mitha; Utami, Ni Wayan Ardiarani; Wijaatmaja, Arya Bagus Mahadwijati (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
The rapid growth of tourism in the 20th century raised awareness of tourism workers and business, as well as tourists to ensure the sustainable development of tourism. Tourism development has two dilemmas, on one side, the tourism industry provides many opportunities in the economic field, economic diversification, increasing income, employment and poverty reduction. On the other hand, tourism can pose a threat to the preservation of cultural and environmental resources, which are vital facilities to attract tourists. Can these two conflicting dynamics be reconciled? This article addresses the management of sustainable tourism in Taman Ujung Soekasada. Sustainable tourism refers to the environmental, economic and socio-cultural aspects of tourism development. Based on observations found that there are sustainable aspects in the tourism management of Taman Ujung Soekasada, which includes the utilization of environmental resources, especially water resources (environmental aspects), socio-cultural preservation and conservation of cultural heritage (socio-cultural aspects) and economic empowerment of local communities both as managers and traders (economic aspects)